Separation of Ink Particles from Waste Paper by Fine-bubbles - Hassan El-Shall; Brij M. Moudgil; Ayman El-Midany (KONA Powder and Particle Journal, 2014)
This article describes the research leading to the development of a new process for flotation deinking of waste paper, including old newsprint (ONP), magazines, etc. The technique involves a simple reagent scheme (ammonium hydroxide or sodium bicarbonate) that can be used at room temperature to generate fine bubbles at the ink/fiber/water interface that help in the ink particle detachment as well as in rendering ink particles hydrophobic. The reagents also act on desorbing organic species (oil) from oil-based ink, thereby stabilizing the bubbles. A self-aeration flotation machine could be used to enhance flotation kinetics. Experimental studies have been conducted to evaluate different operating conditions, including reagent dosage, flotation time, recycling flotation water, etc. The efficiency of the process is evaluated in terms of yield of clean pulp, brightness, and reagent consumption.